ANALYSIS OF FACTORS IN AFFECTING MUZAKKI'S INTEREST IN PAYING PROFESSIONAL ZAKAT FOR CIVIL SERVANTS AT THE KANWIL OF THE MINISTRY OF RELIGION DKI JAKARTA - Nindi Azizah Alfriani; Achmad Fauzi; Mardi Mardi (International Journal of Multidisciplinary Research and Literature, 2022)
This study aims to analyze the effect of religiosity, income and service quality on the interest of muzakki to pay zakat. The research method used is a quantitative method with an associational research approach. Data analysis used classical assumption tests, statistical tests and multiple regression analysis. The sampling technique used was purposive sampling consisting of 191 civil servant respondents at the Regional Office of the Ministry of Religion DKI Jakarta. The data collection is through the distribution of Google Form questionnaires and secondary data in the form of rank order data from the Regional Office of the Ministry of Religion of DKI Jakarta Province. Based on the results of the study partially stated that religiosity has a positive effect on interest in paying zakat, income does not have a positive effect on interest in paying zakat and service quality has a positive effect on interest in paying zakat. And religiosity, income, and service quality positively affect interest in paying zakat